Planning your PhD - Williams, Kate (Palgrave Macmillan, 2015)
This text offers students specific, succinct guidance to the core process and major hurdles involved in undertaking a PhD. As well as offering practical advice, such as how to shape initial ideas, it also encourages students to find and value their own pathways and approaches within academia.